The effect of 36 hours sleep deprivation on dribbling skills of soccer players - Hefzollesan, M.; Ghalehgir, S.; Ekrami, M. (Physical Education of Students, 2013)
The aim of this study is to determine the effect of sleep deprivation on the dribbling skills of football players. To this end, 22 students of Sahand University, with age range (20-24 years) performed dribbling skill in the pre-test and post test stages. In this study to assess this skill, the test "Mor - Christian" has been used. In the first step, subjects conducted the dribble test as pre-test after 8 hours sleep a night. 10 days later, to ensure the validity of tests and test results on the learning effect, subjects did the same test again after 8 hours sleep a night. In the third stage, 36 hours of sleep deprivation as an independent variable imposed on the subjects and then the test was repeated and experimental test results were compared as recorded using paired t-test. The findings showed that 36 hour sleep deprivation decreases dribble implementation skills (p <0.001). Therefore, the findings showed that sleep deprivation can be a devastating effect on dribbling skill.